THE BATTLE OF GAUGAMELA AND THE QUESTION OF VISIBILITY ON THE BATTLEFIELD. (December 2021) - Marciak, Michał; Szypuła, Bartłomiej; Sobiech, Marcin; Pirowski, Tomasz
Abstract : The aim of this paper is to contribute to the long-standing topographical enigma of the identification of Gaugamela. In this study, a GIS method known as viewshed analysis is employed to solve a certain historical problem. 1 According to ancient sources, on the eve of the battle the approaching Macedonian army and the Persian troops that were waiting on the battlefield could not see each other because of intervening hills at a distance of c. 12 km. However, the two armies gained a full view of their respective positions once the Macedonians reached the hills c. six km away from the Persian positions. Our analysis shows that the identification of the battlefield near Tell Gomel, in the Kurdistan Region of Iraq, is consistent with the visibility requirements of the ancient sources, while the previous identifications of the battlefield in the vicinity of Karamleis and Qaraqosh (Stein 1942; Sushko 1936; Zouboulakis 2015, 2016) feature poor results in terms of expected visibility.